Konflik Corporate vs. Society: Analisis terhadap Konflik dalam Kasus Pendirian Pabrik Semen di Kecamatan Sukolilo Kabupaten Pati - Avid Nur Meida; Purwoko .; Budi Setyono (Journal of Politic and Government Studies, 2013)
The attendance of national project’s plan of cement factory construction in Sukolilo, Pati, causes pro-contra reaction in a group of civil servant and in the society that located in the near with the factory location, limestone and clay soil mining. This research is to analyze the conflict between the company and society toward the politic, economic, social, cultural and environment impact that may arise caused by the cement factory construction.This research uses descriptive analysis approach, to illustrate a conflict phenomenon, and aimed to explain it specifically. In collecting data, the writer uses qualitative method by deepen interview. In choosing the informant the writer uses snowball technique or continually asking the information to the people that has interviewed or contacted before until the writer gets enough information.The result of this research shows that the conflict arise caused by the differences of opinion between pro and contra group toward the construction of cement factory’s plan in Sukolilo region, as one of the regions that prioritized in having the raw materials for cement with a good quality. Because of it, the investor interested to exploit the karst soil that contained in Kendeng mountain. In that conflict, not only caused by among the group of society and project initiator but also with the Pati government.Each of the attitude from pro or contra group is influenced by social, politic, economy and culture aspects. The contra group’s attitude appears because of the anxiety about the uncertainty of economy impact like work opportunity, business chance, and prosperity. Besides that environment issue become an important reason, the anxiety of water source missing, sound pollution (noisiness) and also air pollution that have an influence to the health. For it, the natural resource usage that managed by districtgovernment must do in fair and harmonious way. If not, conflict will be happen. In sociocultural way, the society don’t want a transition that influencing social and cultural systems. While, pro group will give support to the investor continuously so that the investor can build cement factory in Sukolilo sub-district that aimed to use Kendeng mountain’s karst soil as the cement raw materials and also can give a job opening to the citizens who live arround the applicant of factory, so that the positive impact from the region construction can make the prosperous society.Keywords: Conflict, Region Construction, Impact